2022
DOI: 10.3389/fendo.2022.870530
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Body Mass Index on the Clinical Outcome of Papillary Thyroid Cancer After High-Dose Radioactive Iodine Therapy

Abstract: ContextObesity has been reported as a potential risk factor for the aggressiveness of papillary thyroid cancer (PTC), but the data gathered so far are conflicting.ObjectiveThe aim of our study was to evaluate the relationship between body mass index (BMI) and aggressiveness of PTC at the diagnosis and clinical outcome.MethodsA total of 337 patients who underwent radioactive iodine (RAI) therapy between March 2017 and May 2020 were recruited. Patients were divided into four groups: underweight (BMI<18.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Gąsior-Perczak et al 30 suggested that obesity was neither associated with the more aggressive clinicopathological features of TC, nor a risk factor for disease progression to more advanced stages, nor a prognostic factor for poor treatment response and clinical outcome. The study of Cao et al 31 on obesity and TC iodine-131 therapy suggested that although obesity may have an additive effect on the aggressiveness of PTC, there was no difference in the treatment response to iodine-131 therapy between obese patients and normal weight patients. In general, although many studies have found that obesity is related to the adverse pathological factors of TC, they do not believe that obesity is related to the risk of TC recurrence, and some studies have different opinions and are controversial.…”
Section: Discussionmentioning
confidence: 98%
“…Gąsior-Perczak et al 30 suggested that obesity was neither associated with the more aggressive clinicopathological features of TC, nor a risk factor for disease progression to more advanced stages, nor a prognostic factor for poor treatment response and clinical outcome. The study of Cao et al 31 on obesity and TC iodine-131 therapy suggested that although obesity may have an additive effect on the aggressiveness of PTC, there was no difference in the treatment response to iodine-131 therapy between obese patients and normal weight patients. In general, although many studies have found that obesity is related to the adverse pathological factors of TC, they do not believe that obesity is related to the risk of TC recurrence, and some studies have different opinions and are controversial.…”
Section: Discussionmentioning
confidence: 98%
“…Recent meta-analyses and subsequent relevant studies are summarized in Table 2. These show that obesity is associated with larger tumor size [14,22 ▪▪ ,23–26], extrathyroidal extension (ETE) [22 ▪▪ ,23,24,26,27], multifocality [22 ▪▪ ,23–27], and advanced stage [24–26]. Two recent meta-analyses reported a significant association with nodal metastases [22 ▪▪ ,23], although another did not [24].…”
Section: Epidemiologic Evidence Of a Relationship Between Excess Body...mentioning
confidence: 97%
“…Most studies have not shown an association between obesity and thyroid cancer outcomes or response to radioactive iodine [22 ▪▪ ,24,25], although, based on a small number of events, one recent study found that those who were obese had greater risk of disease recurrence (RR = 1.98, 95%CI 1.04–3.77) [62]. Indeed, the rates of adverse clinical outcomes for PTC are typically low and larger studies with longer follow-up are needed to reliably evaluate such events.…”
Section: Obesity and Thyroid Cancer Outcomesmentioning
confidence: 99%